2014
DOI: 10.1007/s10151-014-1157-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of colovesical fistulas due to complicated colonic diverticular disease: a systematic review

Abstract: Colovesical fistulas originating from complicated sigmoid diverticular disease are rare. The primary aim of this review was to evaluate the role of laparoscopic surgery in the treatment of this complication. The secondary aim was to determine the best surgical treatment for this disease. A systematic search was conducted for studies published between 1992 and 2012 in PubMed, the Cochrane Register of Controlled Clinical Trials, Scopus, and Publish or Perish. Studies enrolling adults undergoing fully laparoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 39 publications
5
45
1
5
Order By: Relevance
“…The incidence of colovesical fistula is higher in men than in women due to the presence of the uterus between the bladder and colon. Recent studies have reported the efficacy of one-stage resection in laparoscopic surgery occasionally [168][169][170], but the presence of inflammation makes the procedure more difficult than the standard surgery for colorectal cancer. Therefore, the surgery should be performed by skilled surgeons.…”
Section: Cq38: What Is the Definition Of Complicated Colonic Diverticmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of colovesical fistula is higher in men than in women due to the presence of the uterus between the bladder and colon. Recent studies have reported the efficacy of one-stage resection in laparoscopic surgery occasionally [168][169][170], but the presence of inflammation makes the procedure more difficult than the standard surgery for colorectal cancer. Therefore, the surgery should be performed by skilled surgeons.…”
Section: Cq38: What Is the Definition Of Complicated Colonic Diverticmentioning
confidence: 99%
“…Fistulas occur in 4-20% of patients with colonic diverticulitis. rence are the bladder, sigmoid colon, uterus, vagina (after hysterectomy), kidneys, and skin [152,168,169]; with the bladder and sigmoid colon having the highest rates of occurrence. Colovesical fistula very rarely closes spontaneously because the pressure in the colon is much higher than that in the bladder.…”
Section: Cq38: What Is the Definition Of Complicated Colonic Diverticmentioning
confidence: 99%
“…In the present study, an omental interposition was performed in just over one-third of the patients. This technique may reduce the risk of recurrent fistulas by placing healthy, well-vascularized tissue over the surface of the bladder to improve healing [2,[7][8][9]. Given our low leak rates, the use of this procedure may be more Table 3 Postoperative outcomes of patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the bladder component may involve fistulotomy with sutured or stapled repair of the bladder defect, or the bladder can be left to heal via secondary intention. 11 Surgery can be laparoscopic or open. In the first few weeks after fistula formation, friable intra-abdominal adhesions develop that greatly enhance the risk of damage to intra-abdominal organs during surgery.…”
Section: Treatment Of Colovesical Fisulaementioning
confidence: 99%